An explainable deep learning-integrated decision support system for field diagnosis and management of botrytis grey mold in castor - G. Jadesha; Yamanura Madival; R. Mohan Kumar; Anurag Dhole; H.C. Lohithaswa; Mallana Gowda Mallikarjuna; K.B. Palanna; D. Deepak (Computers and Electronics in Agriculture, 2026)

Experimental and ANN-based prediction of the mechanical properties of fly ash geopolymer concrete - Swapnil D. Kurhade; Sachin B. Kandekar; Manoj P. Wagh; Deepak A. Vidhate; Vikas D. Gholap; Subhash V. Patankar (Innovative Infrastructure Solutions, 2026)

7-Hydroxyflavone mitigates partial sciatic nerve ligation–induced neuropathic pain via modulation of oxidative and inflammatory pathways - Ashish D. Tale; Shirish P. Jain; Siddharth V. Kamble; Sachin P. Borikar; Shailesh M. Kewatkar; Deepak K. Lokwani; Satish P. Shelke; Dipak V. Bhusari; Sangameshwar B. Kanthale (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unraveling cellular longevity pathways in poultry under heat stress: functional and computational characterization of the adaptogenic formulation Phytocee™ - K. Shamana; R. Edwin; S. P. Jaishree; D. Prashanth; G. Aboli; M. Deepak (In Silico Pharmacology, 2026)

Ai-powered decision-support system for maize Turcicum Leaf Blight: Novel ensemble models for disease forecasting with integrated fungicide advisory - G. Jadesha; Anupkumar M Bongale; H.C. Lohithaswa; N.B. Prakash; M.K.Prasanna Kumar; D. Deepak; Shreyans S Gadekar; Anurag Dhole; Yamanura Madival; R.Mohan Kumar; Deepak Dharrao (Computers and Electronics in Agriculture, 2025)

Fortifying the frontier: cell wall modifications during plant immunity - Deepak D. Bhandari; Sang-Jin Kim; Federica Brandizzi (Current Opinion in Plant Biology, 2025)

A remote sensing algorithmic framework for characterizing chromophoric dissolved organic matter in lagoon-estuarine systems - Ishan D. Joshi; Abhishek Kumar; Sambit Singh; Susmita Raulo; Tamoghna Acharyya; Deepak R. Mishra (Science of The Total Environment, 2025)

Genetic basis and role of exotic accessions in cultivated cotton fiber quality improvement - Ankush Sharma; Mingrui Xu; Deepak Vitrakoti; Jinesh D. Patel; Peng W. Chee; Andrew H. Paterson (Theoretical and Applied Genetics, 2025)
Key message Exotic Gossypium accessions still harbor QTL‑validated alleles that, combined with CRISPR pyramiding and genomic selection, can break the entrenched fiber length–strength trade‑off. Abstract Cotton’s four independent domestications twice in diploids and twice in allotetraploids offer a natural experiment in fiber improvement. Synthesizing three decades of data, we chart how polyploidy, selection and modern breeding have repeatedly reshaped the Gossypium genome. More than 15,000 quantitative trait locus (QTL) and genome wide association mapping studies (GWAS) hits converge on a handful of chromosomal “hotspots”; new MAGIC, NAM, NIL and long-read resources now narrow these peaks to < 200 kb, resolving causal genes such as GhHOX3, GhZF14 and GhMYB7 . Multi-omics evidence links auxin, ethylene, gibberellin, brassinosteroid and strigolactone signaling to HDZIP IV, MYB, bHLH/HLH and ERF networks that drive fiber initiation, extreme cell elongation and cellulose deposition. Population genomics shows that ~ 40% of favorable fiber alleles are fixed in elite Gossypium hirsutum , yet wild diploids and landraces still harbor variants that could break the length strength trade-off. We propose a three-step roadmap genomic selection, CRISPR gene pyramiding and accelerated introgression to expand cotton’s genetic base and deliver fibers suited to sustainable textile demands.

Therapeutic Potential of High Dose Vitamin C in Cancer: Mechanisms, Clinical Evidence and Future Directions - Ragini D. Singh; Deepak N. Parchwani; Gaurav Sharma; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2025)

Decoding late Quaternary paleoclimatic signatures from the western Bay of Bengal: A multiproxy approach - Nayana V. Haridas; Upasana S. Banerji; D. Padmalal; K. Maya; P. John Kurian; Ravi Bhushan; Ankur J. Dabhi; Deepak Kumar Agarwal; A.K. Sudheer; Ruta B. Limaye; K.P.N. Kumaran (Quaternary International, 2025)

Harvest of algal biomass with bioflocculants for biofuel with upstream and downstream processes: State-of-the-art towards sustainable alternative - Kajol Goria; Richa Kothari; Har Mohan Singh; Deepak Pathania; D. Buddhi; Atul Sharma; V. V. Tyagi (Energy, Ecology and Environment, 2025)

Morpho-cultural variability, pathogenicity and molecular identification of Phytophthora cajani isolates causing blight disease of pigeonpea in India - Raj K. Mishra; Abhishek Bohra; Deepak Kumar; A.K. Parihar; K.K. Hazra; Sonika Pandey; Monika Mishra; Satheesh Naik SJ; Nidhi Kumari; D. Datta; Smita Tiwari; Naimuddin; et al. (Physiological and Molecular Plant Pathology, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Conservation of native tree species in the agroforest of rice-based agroecosystems will contribute to sustainable agriculture - Merlin Lopus; Amit Kushwaha; M. D. Reshma; Subaiba Shafi; Abdulla Habeeb; Telna Sebastian; Deepak Jaiswal; V. Shakeela (Biodiversity and Conservation, 2025)

Correction: Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2025)

Intelligent growth of holy basil: an iot-based hydroponics system empowered by the CRL-SHS Algorithm - T. Kumaragurubaran; Rahul Chiranjeevi; Elangovan D; Deepak Kumar K (Earth Science Informatics, 2025)

Bias correction of satellite precipitation estimates using Mumbai-MESONET observations: A Random Forest approach - Deepak Singh Bisht; D. Preveen Kumar; K. Amarjyothi; Upal Saha (Atmospheric Research, 2025)

Genome-wide exploration of soybean domestication traits: integrating association mapping and SNP × SNP interaction analyses - Abhinandan S. Patil; Manoj D. Oak; Shreyash Gijare; Aditya Gobade; Santosh Jaybhay; Vilas D. Surve; Suresha P. G.; Dattatraya Salunkhe; Balasaheb N. Waghmare; Bhanudas Idhol; Ravindra M. Patil; Deepak Pawar (Plant Molecular Biology, 2025)

Smart solutions for maize farmers: Machine learning-enabled web applications for downy mildew management and enhanced crop yield in India - Jadesha G; Edel Castelino; P. Mahadevu; M.S. Kitturmath; H.C. Lohithaswa; Chikkappa G. Karjagi; Deepak D (European Journal of Agronomy, 2025)

Ultrahigh energy density in high-temperature polymer dielectric reinforced by bilayer nanocoating - Yifei Wang; Thomas Linker; K.M. Abu Hurayra Lizu; Luis A. Ortiz-Flores; Deepak Kamal; Jierui Zhou; Hiep Nguyen; Chuanyang Li; Wenqiang Gao; Antigoni Konstantinou; Lihua Chen; Bryan D. Huey; et al. (Chemical Engineering Journal, 2025)

In-silico identification and exploration of small molecule coumarin-1,2,3-triazole hybrids as potential EGFR inhibitors for targeting lung cancer - Sunil Kumar; Iqra Ali; Faheem Abbas; Faiza Shafiq; Ashok Kumar Yadav; Manjunath D. Ghate; Deepak Kumar (Molecular Diversity, 2024)

Neck extensor myopathy- a treatable cause of dropped head syndrome - Nibu Varghese; Vimal Chandraghosh K D; Deepak Menon; Abdurahiman P; Anoop Kattadimmal; Jubin Mathew; Shobika B S; Nyla Mary Babu (Acta Neurologica Belgica, 2024)

How changes projected by climate models can inform climate adaptation and marine sanctuary management: A collaborative prototype methodology - Daniel Morris; Deepak Cherian; Frederic Castruccio; Curt Davidson; Joanie Kleypas; Kristen Krumhardt; Melissa Moulton; Ryan D. Williamson; Sarah Zohdy; Kelly Dunning (Journal of Environmental Management, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Strategic administration of antioxidant multiminerals and vitamins to transitional buffaloes augments antioxidant and udder defense mechanisms in early lactation - D. Deepak; U.K. De; T.K. Sarkar; S. Katoch; J.K. John; V.K. Sarkar (Research in Veterinary Science, 2024)

Silica and polymer coated controlled release nitrogen-phosphorus fertilizer for improving nutrient and water use efficiency in semi-arid India - Avijit Ghosh; Amit K. Singh; R.V. Kumar; Prashant D. Singh; Sukanya Misra; Safik Ahamed; Deepak Ojha; Amaresh Chandra; Ranjan Bhattacharyya (Journal of Environmental Chemical Engineering, 2024)

Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2024)
Zinc (Zn) biofortification of rice can address Zn malnutrition in Asia. Identification and introgression of QTLs for grain Zn content and yield (YLD) can improve the efficiency of rice Zn biofortification. In four rice populations we detected 56 QTLs for seven traits by inclusive composite interval mapping (ICIM), and 16 QTLs for two traits (YLD and Zn) by association mapping. The phenotypic variance (PV) varied from 4.5% ( qPN 4.1 ) to 31.7% ( qPH 1.1 ). qDF 1.1 , qDF 7.2 , qDF 8.1 , qPH 1.1 , qPH 7.1 , qPL 1.2 , qPL 9.1, qZn 5.1 , qZn 5.2 , qZn 6.1 and qZn 7.1 were identified in both dry and wet seasons; qZn 5.1 , qZn 5.2 , qZn 5.3, qZn 6.2, qZn 7.1 and qYLD 1.2 were detected by both ICIM and association mapping. qZn 7.1 had the highest PV (17.8%) and additive effect (2.5 ppm). Epistasis and QTL co-locations were also observed for different traits. The multi-trait genomic prediction values were 0.24 and 0.16 for YLD and Zn respectively. qZn 6.2 was co-located with a gene ( OsHMA2 ) involved in Zn transport. These results are useful for Zn biofortificatiton of rice.

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Clinical, epidemiological, and molecular investigation of Kyasanur forest disease from Karnataka state, India during 2018-2019 - Ashok Munivenkatappa; Pragya D. Yadav; Rima R. Sahay; Kiran SK; Anita M. Shete; Deepak Y. Patil; Sreelekshmy Mohandas; Rajlaxmi Jain; Savita Patil; Diamond P. Sinha; Manjunatha M. Jayaswamy (Infectious Diseases, 2024)

A Quality by Design Approach for Developing SNEDDS Loaded with Vemurafenib for Enhanced Oral Bioavailability - Chakradhar JVUS; Naresh Kothuri; Sanjay Singh; Sonia Verma; Hasham Shafi; D. V. Siva Reddy; Ashwini Kedar; Rafquat Rana; Keerti Mishra; Deepak Sharma; Manish K. Chourasia (AAPS PharmSciTech, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Discovery of a new species of dwarf frog (Anura: Ceratobatrachidae: Alcalus ) extends the northwestern distributional limits of the genus to Northeast India - Bitupan Boruah; Surya Narayanan; Jason D. Gerard; Abhijit Das; V. Deepak (Systematics and Biodiversity, 2023)

Association of the Human Leptin Receptor Gene (rs1137101; Gln223Arg) Polymorphism and Circulating Leptin in Patients with Metabolic Syndrome in the Indian Population - Deepak Parchwani; Sagar Dholariya; Digishaben D. Patel; Ashishkumar Agravatt; Jayant Uperia; Tanishk Parchwani; Ragini Singh; Madhuri Radadiya; Yash Desai (Indian Journal of Clinical Biochemistry, 2023)

Advances and prospects of platelet-rich plasma therapy in veterinary ophthalmology - Khan Sharun; Deepak Chandran; K. M. Manjusha; Pratheesh D. Mankuzhy; Rohit Kumar; Abhijit M. Pawde; Kuldeep Dhama; Hussein M. El-Husseiny; Amarpal (Veterinary Research Communications, 2023)

Peach (Prunus persica (L.) Batsch) seeds and kernels as potential plant-based functional food ingredients: A review of bioactive compounds and health-promoting activities - Neeraj Kumari; Radha; Manoj Kumar; Sunil Puri; Baohong Zhang; Nadeem Rais; Ashok Pundir; Deepak Chandran; Priya Raman; Sangram Dhumal; Abhijit Dey; Marisennayya Senapathy; et al. (Food Bioscience, 2023)

Enhanced pearl millet yield stability, water use efficiency and soil microbial activity using superabsorbent polymers and crop residue recycling across diverse ecologies - R.S. Bana; Minakshi Grover; Deepak Singh; Shanti D. Bamboriya; Samarth Godara; Manoj Kumar; Anil Kumar; Seema Sharma; P.S. Shekhawat; Dinesh Lomte; H.M. Bhuva; Sadhana R. Babar; et al. (European Journal of Agronomy, 2023)

Preliminary study of the interactive effects of THC and ethanol on self-reported ability and simulated driving, subjective effects, and cardiovascular responses - Ashley M. Schnakenberg Martin; L. Taylor Flynn; Esra Sefik; Christina Luddy; Jose Cortes-Briones; Patrick D. Skosnik; Brian Pittman; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2023)

Heavy and less common metals in rainwater and the kinetics of the oxidation of hydrogen sulfide by oxygen in rainwater medium - Deepak Singh Rathore; Paramjeet Singh; C. D. Misra; C. P. Singh Chandel; Swati Bugalia; Krishna Swarup Gupta (Environmental Monitoring and Assessment, 2023)

Foliar zinc fertilization improves yield, biofortification and nutrient-use efficiency of upland rice - Akshay Kumar Yogi; Ram Swaroop Bana; Shanti D. Bamboriya; Ram L. Choudhary; Alison M. Laing; Deepak Singh; Samarth Godara; Subhash Babu; Amresh Chaudhary (Nutrient Cycling in Agroecosystems, 2023)

Mitigation of nitrous oxide emissions in grazing systems through nitrification inhibitors: a meta-analysis - Johnny R. Soares; Bruna R. Souza; André M. Mazzetto; Marcelo V. Galdos; Dave R. Chadwick; Eleanor E. Campbell; Deepak Jaiswal; Julianne C. Oliveira; Leonardo A. Monteiro; Murilo S. Vianna; Rubens A. C. Lamparelli; Gleyce K. D. A. Figueiredo; et al. (Nutrient Cycling in Agroecosystems, 2023)
Grasslands are the largest contributor of nitrous oxide (N 2 O) emissions in the agriculture sector due to livestock excreta and nitrogen fertilizers applied to the soil. Nitrification inhibitors (NIs) added to N input have reduced N 2 O emissions, but can show a range of efficiencies depending on climate, soil, and management conditions. A meta-analysis study was conducted to investigate the factors that influence the efficiency of NIs added to fertilizer and excreta in reducing N 2 O emissions, focused on grazing systems. Data from peer-reviewed studies comprising 2164 N 2 O emission factors (EFs) of N inputs with and without NIs addition were compared. The N 2 O EFs varied according to N source (0.0001–8.25%). Overall, NIs reduced the N 2 O EF from N addition by 56.6% (51.1–61.5%), with no difference between NI types (Dicyandiamide—DCD; 3,4-Dimethylpyrazole phosphate—DMPP; and Nitrapyrin) or N source (urine, dung, slurry, and fertilizer). The NIs were more efficient in situations of high N 2 O emissions compared with low; the reduction was 66.0% when EF > 1.5% of N applied compared with 51.9% when EF ≤ 0.5%. DCD was more efficient when applied at rates > 10 kg ha −1 . NIs were less efficient in urine with lower N content (≤ 7 g kg −1 ). NI efficiency was negatively correlated with soil bulk density, and positively correlated with soil moisture and temperature. Better understanding and management of NIs can optimize N 2 O mitigation in grazing systems, e.g., by mapping N 2 O risk and applying NI at variable rate, contributing to improved livestock sustainability.

Assessing the Effectiveness of Large-Scale Environmental Restoration: Challenges and Opportunities - Holly S. Greening; Kenneth L. Heck; Larry D. McKinney; Heida L. Diefenderfer; Walter R. Boynton; Barbara A. Kleiss; Deepak R. Mishra; Albert A. George; Bethany A. Carl Kraft; Cathy A. Kling; Laura A. Windecker (Estuaries and Coasts, 2023)

Cases of SARS-CoV-2 reinfection with Omicron BA.2 post breakthrough infection with Delta and Kappa variants - Rima R. Sahay; Deepak Y. Patil; Gajanan N. Sapkal; Anita M. Shete; Pragya D. Yadav (Infectious Diseases, 2023)

Toxicity potential evaluation of ethyl acetate extract of Cymodocea serrulata against the mosquito vectors vis-a-vis zebrafish embryos and Artemia salina cysts - V. Amutha; D. Aiswarya; P. Deepak; R. Selvaraj; C. Tamilselvan; P. Perumal; G. Balasubramani (South African Journal of Botany, 2023)

Synthesis of energy rich fuel additive from biomass derived levulinic acid and furfuryl alcohol using novel tin-exchanged heteropoly acid supported on titania nanotubes as catalyst - Deepak S. Desai; Ganapati D. Yadav (Fuel, 2023)

Function of FMRP Domains in Regulating Distinct Roles of Neuronal Protein Synthesis - Michelle Ninochka D’Souza; Sarayu Ramakrishna; Bindushree K. Radhakrishna; Vishwaja Jhaveri; Sreenath Ravindran; Lahari Yeramala; Deepak Nair; Dasaradhi Palakodeti; Ravi S. Muddashetty (Molecular Neurobiology, 2022)

A Molecular Insight of the Role of PIN-1 Promoter Polymorphism (− 667C > T; rs2233679) in Chronic Kidney Disease Patients with Secondary Hyperparathyroidism - Digishaben D. Patel; Deepak Parchwani; Uday Vachhani; Tanishk Parchwani; Pratik Raghavani; Ajay Rajput; Sagar Dholariya; Ragini Singh (Indian Journal of Clinical Biochemistry, 2022)

Correction to: Psychedelics: Old trips, new destinations in psychopharmacology research - Harriet de Wit; Deepak Cyril D’Souza (Psychopharmacology, 2022)

Psychedelics: Old trips, new destinations in psychopharmacology research - Harriet de Wit; Deepak Cyril D’Souza (Psychopharmacology, 2022)

Sex differences in the acute effects of intravenous (IV) delta-9 tetrahydrocannabinol (THC) - Anahita Bassir Nia; Maria J. Orejarena; Leigh Flynn; Christina Luddy; Deepak Cyril D’Souza; Patrick D. Skosnik; Brian Pittman; Mohini Ranganathan (Psychopharmacology, 2022)

Editorial - Deepak Cyril D’Souza; Helen Valerie Curran (Psychopharmacology, 2022)

Utility of P-SEP, sTREM-1 and suPAR as Novel Sepsis Biomarkers in SARS-CoV-2 Infection - Sagar Dholariya; Deepak N. Parchwani; Ragini Singh; Madhuri Radadiya; C. D. S. Katoch (Indian Journal of Clinical Biochemistry, 2022)

The DNA Replication, Repair, and Recombination Pathway Genes Modulating Yield and Stress Tolerance Traits in Chickpea - Udita Basu; Akash Sharma; Deepak Bajaj; Naveen Malik; Uday Chand Jha; Hari D. Upadhyaya; Swarup K. Parida (Plant Molecular Biology Reporter, 2022)

The feasibility of using a low-cost near-infrared, sensitive, consumer-grade digital camera mounted on a commercial UAV to assess Bambara groundnut yield - Shaikh Yassir Yousouf Jewan; Vinay Pagay; Lawal Billa; Stephen D. Tyerman; Deepak Gautam; Debbie Sparkes; Hui Hui Chai; Ajit Singh (International Journal of Remote Sensing, 2022)

Analysis of the Pattern, Alliance and Risk of rs1799752 (ACE I/D Polymorphism) with Essential Hypertension - Digishaben D. Patel; Deepak N. Parchwani; Nirupama Dikshit; Tanishk Parchwani (Indian Journal of Clinical Biochemistry, 2022)

Friedel-crafts acylation of furan using chromium-exchanged dodecatungstophosphoric acid: effect of support, mechanism and kinetic modelling - Deepak S. Desai; Ganapati D. Yadav (Clean Technologies and Environmental Policy, 2021)

Impact of heat and drought stress on phenological development and yield in bread wheat - K. J. Yashavanthakumar; Vijendra S. Baviskar; Sudhir Navathe; Ravindra M. Patil; Juned H. Bagwan; Deepak N. Bankar; Vitthal D. Gite; K. Gopalareddy; Chandra Nath Mishra; H. M. Mamrutha; Sanjay Kumar Singh; Shreenivas A. Desai; et al. (Plant Physiology Reports, 2021)

Coronavirus Disease (Covid-19) Associated Mucormycosis (CAM): Case Report and Systematic Review of Literature - Deepak Garg; Valliappan Muthu; Inderpaul Singh Sehgal; Raja Ramachandran; Harsimran Kaur; Ashish Bhalla; Goverdhan D. Puri; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2021)

Hydrogeochemical evaluation, suitability, and health risk assessment of groundwater in the watershed of Godavari basin, Maharashtra, Central India - Deepali Marghade; Deepak. B. Malpe; Karunanidhi Duraisamy; Pravin D. Patil; Peiyue Li (Environmental Science and Pollution Research, 2021)

In an exploratory randomized, double-blind, placebo-controlled, cross-over study, psychoactive doses of intravenous delta-9-tetrahydrocannabinol fail to produce antinociceptive effects in healthy human volunteers - Emmanuelle A. D. Schindler; Ashley M. Schnakenberg Martin; R. Andrew Sewell; Mohini Ranganathan; Anna DeForest; Brian P. Pittman; Albert Perrino; Deepak C. D’Souza (Psychopharmacology, 2020)

Methods and approaches to advance soil macroecology - Hannah J. White; Lupe León‐Sánchez; Victoria J. Burton; Erin K. Cameron; Tancredi Caruso; Luís Cunha; Tara Dirilgen; Stephanie D. Jurburg; Ruth Kelly; Deepak Kumaresan; Raúl Ochoa‐Hueso; Alejandro Ordonez; et al. (Global Ecology and Biogeography, 2020)
Motivation and aim Soil biodiversity is central to ecosystem function and services. It represents most of terrestrial biodiversity and at least a quarter of all biodiversity on Earth. Yet, research into broad, generalizable spatial and temporal patterns of soil biota has been limited compared to aboveground systems due to complexities of the soil system. We review the literature and identify key considerations necessary to expand soil macroecology beyond the recent surge of global maps of soil taxa, so that we can gain greater insight into the mechanisms and processes shaping soil biodiversity. We focus primarily on three groups of soil taxa (earthworms, mycorrhizal fungi and soil bacteria) that represent a range of body sizes and ecologies, and, therefore, interact with their environment at different spatial scales. Results The complexities of soil, including fine‐scale heterogeneity, 3‐D habitat structure, difficulties with taxonomic delimitation, and the wide‐ranging ecologies of its inhabitants, require the classical macroecological toolbox to be expanded to consider novel sampling, molecular identification, functional approaches, environmental variables, and modelling techniques. Main conclusions Soil provides a complex system within which to apply macroecological research, yet, it is this property that itself makes soil macroecology a field ripe for innovative methodologies and approaches. To achieve this, soil‐specific data, spatio‐temporal, biotic, and abiotic considerations are necessary at all stages of research, from sampling design to statistical analyses. Insights into whole ecosystems and new approaches to link genes, functions and diversity across spatial and temporal scales, alongside methodologies already applied in aboveground macroecology, invasion ecology and aquatic ecology, will facilitate the investigation of macroecological processes in soil biota, which is key to understanding the link between biodiversity and ecosystem functioning in terrestrial ecosystems.

Formulation, Optimization, and Evaluation of Allopurinol-Loaded Bovine Serum Albumin Nanoparticles for Targeting Kidney in Management of Hyperuricemic Nephrolithiasis - Gurpreet Kandav; D. C. Bhatt; Deepak Kumar Jindal; Shailendra Kumar Singh (AAPS PharmSciTech, 2020)

Assessment of yield gaps on global grazed‐only permanent pasture using climate binning - Leonardo A. Monteiro; Andrew M. Allee; Eleanor E. Campbell; Lee R. Lynd; Johnny R. Soares; Deepak Jaiswal; Julianne de Castro Oliveira; Murilo dos Santos Vianna; Ashley E. Morishige; Gleyce K. D. A. Figueiredo; Rubens A. C. Lamparelli; Nathaniel D. Mueller; et al. (Global Change Biology, 2020)
To meet rising demands for agricultural products, existing agricultural lands must either produce more or expand in area. Yield gaps (YGs)—the difference between current and potential yield of agricultural systems—indicate the ability to increase output while holding land area constant. Here, we assess YGs in global grazed‐only permanent pasture lands using a climate binning approach. We create a snapshot of circa 2000 empirical yields for meat and milk production from cattle, sheep, and goats by sorting pastures into climate bins defined by total annual precipitation and growing degree‐days. We then estimate YGs from intra‐bin yield comparisons. We evaluate YG patterns across three FAO definitions of grazed livestock agroecosystems (arid, humid, and temperate), and groups of animal production systems that vary in animal types and animal products. For all subcategories of grazed‐only permanent pasture assessed, we find potential to increase productivity several‐fold over current levels. However, because productivity of grazed pasture systems is generally low, even large relative increases in yield translated to small absolute gains in global protein production. In our dataset, milk‐focused production systems were found to be seven times as productive as meat‐focused production systems regardless of animal type, while cattle were four times as productive as sheep and goats regardless of animal output type. Sustainable intensification of pasture is most promising for local development, where large relative increases in production can substantially increase incomes or “spare” large amounts of land for other uses. Our results motivate the need for further studies to target agroecological and economic limitations on productivity to improve YG estimates and identify sustainable pathways toward intensification.

Targeting kidneys by superparamagnetic allopurinol loaded chitosan coated nanoparticles for the treatment of hyperuricemic nephrolithiasis - Gurpreet Kandav; D. C. Bhatt; Deepak Kumar Jindal (DARU Journal of Pharmaceutical Sciences, 2019)

Highs and lows of cannabinoid-dopamine interactions: effects of genetic variability and pharmacological modulation of catechol-O-methyl transferase on the acute response to delta-9-tetrahydrocannabinol in humans - Mohini Ranganathan; Joao P. De Aquino; Jose A. Cortes-Briones; Rajiv Radhakrishnan; Brian Pittman; Savita Bhakta; Deepak C. D’Souza (Psychopharmacology, 2019)

Genome-wide cis-regulatory signatures for modulation of agronomic traits as exemplified by drought yield index (DYI) in chickpea - Akash Sharma; Udita Basu; Naveen Malik; Anurag Daware; Virevol Thakro; Laxmi Narnoliya; Deepak Bajaj; Shailesh Tripathi; V. S. Hegde; Hari D. Upadhyaya; Akhilesh K. Tyagi; Swarup K. Parida (Functional & Integrative Genomics, 2019)

Effects of haloperidol on the delta-9-tetrahydrocannabinol response in humans: a responder analysis - Swapnil Gupta; Joao P. De Aquino; Deepak C. D’Souza; Mohini Ranganathan (Psychopharmacology, 2019)

CLAVATA signaling pathway genes modulating flowering time and flower number in chickpea - Udita Basu; Laxmi Narnoliya; Rishi Srivastava; Akash Sharma; Deepak Bajaj; Anurag Daware; Virevol Thakro; Naveen Malik; Hari D. Upadhyaya; Shailesh Tripathi; V. S. Hegde; Akhilesh K. Tyagi; et al. (Theoretical and Applied Genetics, 2019)

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

Reduction of the carbon footprint of college freshman diets after a food-based environmental science course - Jennifer A. Jay; Raffaella D’Auria; J. Cully Nordby; David Andy Rice; David A. Cleveland; Anthony Friscia; Sophie Kissinger; Marc Levis; Hannah Malan; Deepak Rajagopal; Joel R. Reynolds; Wendelin Slusser; et al. (Climatic Change, 2019)

Cytological and immunocytological detection and differentiation of Marek’s disease and lymphoid leucosis in poultry - M. Asok Kumar; M. Palanivelu; R. Barathidasan; Deepak Kumar; S. D. Singh; Shyma K. Lateef; Rajendra Singh; K. Dhama (VirusDisease, 2018)

A cytogenetic photomap from ovarian nurse cell polytene chromosome of Anopheles stephensi (Diptera: Culicidae): a comparative study - Deepak Sanil; Vinaya Shetty; D. V. Purushothama; N. J. Shetty (The Nucleus, 2018)

The effects of cannabidiol (CBD) on cognition and symptoms in outpatients with chronic schizophrenia a randomized placebo controlled trial - Douglas L. Boggs; Toral Surti; Aarti Gupta; Swapnil Gupta; Mark Niciu; Brian Pittman; Ashley M. Schnakenberg Martin; Halle Thurnauer; Andrew Davies; Deepak C. D’Souza; Mohini Ranganathan (Psychopharmacology, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Analysis of Association of Angiotensin II Type 1 Receptor Gene A1166C Gene Polymorphism with Essential Hypertension - Deepak N. Parchwani; Digisha D. Patel; Jairam Rawtani; Dharmveer Yadav (Indian Journal of Clinical Biochemistry, 2018)

Genetic dissection of plant growth habit in chickpea - Hari D. Upadhyaya; Deepak Bajaj; Rishi Srivastava; Anurag Daware; Udita Basu; Shailesh Tripathi; Chellapilla Bharadwaj; Akhilesh K. Tyagi; Swarup K. Parida (Functional & Integrative Genomics, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Identifying Transcription Factor Genes Associated with Yield Traits in Chickpea - Philanim Wungmarong Shimray; Deepak Bajaj; Rishi Srivastava; Anurag Daware; Hari D. Upadhyaya; Rajendra Kumar; Chellapilla Bharadwaj; Akhilesh K. Tyagi; Swarup K. Parida (Plant Molecular Biology Reporter, 2017)

High-risk human papillomavirus types in HIV-infected and HIV-uninfected young women in KwaZulu-Natal, South Africa: implications for vaccination - Joyce N Mbatha; Myra Taylor; Elisabeth Kleppa; Kristine Lillebo; Hashini N Galapaththi-Arachchige; Deepak Singh; Eyrun F Kjetland; Marc F D Baay; Zilungile L Mkhize-Kwitshana (Infectious Diseases, 2017)

Comparative diagnostic evaluation of OMP31 gene based TaqMan® real-time PCR assay with visual LAMP assay and indirect ELISA for caprine brucellosis - Suman Saini; V. K. Gupta; K. Gururaj; D. D. Singh; R. V. S. Pawaiya; N. K. Gangwar; A. K. Mishra; Deepak Dwivedi; Dimple Andani; Ashok Kumar; T. K. Goswami (Tropical Animal Health and Production, 2017)

Preferential binding to dopamine D3 over D2 receptors by cariprazine in patients with schizophrenia using PET with the D3/D2 receptor ligand [11C]-(+)-PHNO - Ragy R. Girgis; Mark Slifstein; Deepak D’Souza; Yih Lee; Antonia Periclou; Parviz Ghahramani; István Laszlovszky; Suresh Durgam; Nika Adham; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; et al. (Psychopharmacology, 2016)
Rationale Second-generation antipsychotics occupy dopamine D 2 receptors and act as antagonists or partial agonists at these receptors. While these drugs alleviate positive symptoms in patients with schizophrenia, they are less effective for treating cognitive deficits and negative symptoms. Dopamine D 3 receptors are highly expressed in areas of the brain thought to play a role in the regulation of motivation and reward-related behavior. Consequently, the dopamine D 3 receptor has become a target for treating negative symptoms in combination with D 2 antagonism to treat positive symptoms in patients with schizophrenia. Objective The purpose of this study was to determine the cariprazine receptor occupancies in brain for D 2 and D 3 receptors in patients with schizophrenia. Methods Using [ 11 C]-(+)-PHNO as a radioligand, positron emission tomography (PET) scans were performed in eight patients at baseline and postdose on days 1, 4, and 15. Plasma and cerebrospinal fluid (CSF) samples were analyzed for cariprazine concentrations. Results A monotonic dose-occupancy relationship was observed for both receptor types. After 2 weeks of treatment, near complete (∼100 %) occupancies were observed for both receptors at a dose of 12 mg/day. At the lowest cariprazine dose (1 mg/day), mean D 3 and D 2 receptor occupancies were 76 and 45 %, respectively, suggesting selectivity for D 3 over D 2 receptors at low doses. An exposure-response analysis found a ∼3-fold difference in EC 50 (D 3 = 3.84 nM and D 2 = 13.03 nM) in plasma after 2 weeks of dosing. Conclusion This PET imaging study in patients with schizophrenia demonstrated that cariprazine is a D 3 -preferring dual D 3 /D 2 receptor partial agonist.

Association of Mbo I-RFLP at the Renin Locus (rs2368564) with Essential Hypertension - Deepak N. Parchwani; Digisha D. Patel; Jairam Rawtani; Nirupama Dikshit (Indian Journal of Clinical Biochemistry, 2016)

In vitro evaluation of anticancer properties of exopolysaccharides from Lactobacillus acidophilus in colon cancer cell lines - Venkataraman Deepak; Sharavan Ramachandran; Reham Mohammed Balahmar; Sureshbabu Ram Kumar Pandian; Shiva D. Sivasubramaniam; Hariharan Nellaiah; Krishnan Sundar (In Vitro Cellular & Developmental Biology - Animal, 2016)

The early identification of psychosis: can lessons be learnt from cardiac stress testing? - Swapnil Gupta; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2016)

A genome-scale integrated approach aids in genetic dissection of complex flowering time trait in chickpea - Hari D. Upadhyaya; Deepak Bajaj; Shouvik Das; Maneesha S. Saxena; Saurabh Badoni; Vinod Kumar; Shailesh Tripathi; C. L. L. Gowda; Shivali Sharma; Akhilesh K. Tyagi; Swarup K. Parida (Plant Molecular Biology, 2015)

Design, synthesis of quinolinyl Schiff bases and azetidinones as enoyl ACP-reductase inhibitors - Shrinivas D. Joshi; Uttam A. More; Deepak Parkale; Tejraj M. Aminabhavi; Andanappa K. Gadad; Mallikarjuna N. Nadagouda; Rahul Jawarkar (Medicinal Chemistry Research, 2015)

A natural rice rhizospheric bacterium abates arsenic accumulation in rice (Oryza sativa L.) - Venkatachalam Lakshmanan; Deepak Shantharaj; Gang Li; Angelia L. Seyfferth; D. Janine Sherrier; Harsh P. Bais (Planta, 2015)

Homology modeling and molecular docking studies of ArnA protein from Erwinia amylovora: role in polymyxin antibiotic resistance - Kailas D. Sonawane; Rishikesh S. Parulekar; Radhika S. Malkar; Pranhita R. Nimbalkar; Sagar H. Barage; Deepak B. Jadhav (Journal of Plant Biochemistry and Biotechnology, 2015)

Tidal Influence on the Diel Vertical Migration Pattern of Zooplankton in a Tropical Monsoonal Estuary - G. Vineetha; R. Jyothibabu; N. V. Madhu; K. K. Kusum; P. M. Sooria; A. Shivaprasad; P. D. Reny; M. P. Deepak (Wetlands, 2015)

Genetic Predisposition to Diabetic Nephropathy: Evidence for a Role of ACE (I/D) Gene Polymorphism in Type 2 Diabetic Population from Kutch Region - Deepak N. Parchwani; Kamlesh M. Palandurkar; D. Hema Chandan Kumar; Darshan J. Patel (Indian Journal of Clinical Biochemistry, 2015)

Optimization and purification of anticancer enzyme L-glutaminase from Alcaligenes faecalis KLU102 - Sureshbabu Ram Kumar Pandian; Venkataraman Deepak; Shiva D. Sivasubramaniam; Hariharan Nellaiah; Krishnan Sundar (Biologia, 2014)

LHRH-Conjugated Micelles for Targeted Delivery of Antiandrogen to Treat Advanced Prostate Cancer - Di Wen; Deepak Chitkara; Hao Wu; Michael Danquah; Renukadevi Patil; Duane D. Miller; Ram I. Mahato (Pharmaceutical Research, 2014)

Effects of Δ9-tetrahydrocannabinol in individuals with a familial vulnerability to alcoholism - Mohini Ranganathan; R. Andrew Sewell; Michelle Carbuto; Jacqueline Elander; Ashley Schnakenberg; Rajiv Radhakrishnan; Brian Pittman; Deepak Cyril D’Souza (Psychopharmacology, 2014)

Crimean-Congo Hemorrhagic Fever: Current Scenario in India - Pragya D. Yadav; Chandrashekhar G. Raut; Deepak Y. Patil; Triparna D Majumdar; Devendra T. Mourya (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Spicing things up: synthetic cannabinoids - Max Spaderna; Peter H. Addy; Deepak Cyril D’Souza (Psychopharmacology, 2013)

Concomitant antibiotic usage does not augment the risk of inflammatory bowel disease with isotretinoin treatment for acne: a review of the Food and Drug Administration Adverse Event Reporting System - Derrick J. Stobaugh; Parakkal Deepak; Eli D. Ehrenpreis (European Journal of Clinical Pharmacology, 2013)

The safety of studies with intravenous Δ9-tetrahydrocannabinol in humans, with case histories - Michelle Carbuto; R. Andrew Sewell; Ashley Williams; Kim Forselius-Bielen; Gabriel Braley; Jacqueline Elander; Brian Pittman; Ashley Schnakenberg; Savita Bhakta; Edward Perry; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2012)

Bioactive caffeic acid esters from Glycyrrhiza glabra - Surajit Dey; Mundkinajeddu Deepak; Manjunath Setty; Prashanth D’Souza; Amit Agarwal; Gopal Krishna Sangli (Natural Product Research, 2009)

A Thermostable Metal-Tolerant Laccase with Bioremediation Potential from a Marine-Derived Fungus - Donna D’Souza-Ticlo; Deepak Sharma; Chandralata Raghukumar (Marine Biotechnology, 2009)

Modelling psychosis - H. Valerie Curran; Deepak Cyril D’Souza; Trevor W. Robbins; Paul Fletcher (Psychopharmacology, 2009)

The effects of cannabinoids on serum cortisol and prolactin in humans - Mohini Ranganathan; Gabriel Braley; Brian Pittman; Thomas Cooper; Edward Perry; John Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2009)

Preliminary evidence of cannabinoid effects on brain-derived neurotrophic factor (BDNF) levels in humans - Deepak Cyril D’Souza; Brian Pittman; Edward Perry; Arthur Simen (Psychopharmacology, 2009)

Effects of haloperidol on the behavioral, subjective, cognitive, motor, and neuroendocrine effects of Δ-9-tetrahydrocannabinol in humans - Deepak Cyril D’Souza; Gabriel Braley; Rebecca Blaise; Michael Vendetti; Stephen Oliver; Brian Pittman; Mohini Ranganathan; Savita Bhakta; Zoran Zimolo; Thomas Cooper; Edward Perry (Psychopharmacology, 2008)

The acute effects of cannabinoids on memory in humans: a review - Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Greater vulnerability to the amnestic effects of ketamine in males - Celia J. A. Morgan; Edward B. Perry; Hyung-Sang Cho; John H. Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Absence of behavioral sensitization in healthy human subjects following repeated exposure to ketamine - Hyun-Sang Cho; Deepak C. D’Souza; Ralitza Gueorguieva; Edward B. Perry; Steven Madonick; Laurence P. Karper; Anissa Abi-Dargham; Aysenil Belger; Walid Abi-Saab; Deborah Lipschitz; Alexandre Bennet; John P. Seibyl; et al. (Psychopharmacology, 2005)

Antibodies against free radical modified DNA in cancer patients - A. D. Deepak; Moinuddin; S. A. Siddiqui; A. Ali (Indian Journal of Clinical Biochemistry, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)